Prioritizing chemicals for developmental neurotoxicity by integrating data from a new approach methods (NAMs) battery covering key cellular events in neurodevelopment - Laura A. Hall; Jui-Hua Hsieh; Skylar W. Marvel; Mamta Behl; Ellen Fritsche; Katharina Koch; Anna Kreutz; Marcel Leist; Arantza Muriana; Timothy J. Shafer; Jason P. Stanko; Robert C. Sills; et al. (NeuroToxicology, 2026)

Data-driven cost analysis of heat exchanger network retrofits and utility supply at non-continuous sites - Keegan Keysers Hall; Isaac Severinsen; Timothy Gordon Walmsley (Clean Technologies and Environmental Policy, 2026)

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Clean co-combustion of glycerol and methanol blends using a novel fuel-flexible injector - Timothy Hall; Derek Williams; S M Rafiul Islam; Ishaan Patel; Caleb Chakmakjian; Lulin Jiang (Fuel, 2024)

Monitoring spore washoff during a biological contamination incident response using automated stormwater samplers and sensors to predict contamination movement - Anne M. Mikelonis; John Hall; Chris A. Dunn; Timothy McArthur; Garrett Wiley; Chelsea L. Hintz; Joshua Steenbock; Shannon Serre; Michael Worth Calfee; Michael Pirhalla (Science of The Total Environment, 2023)

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Inferred vehicular emissions at a near-road site: Impacts of COVID-19 restrictions, traffic patterns, and ambient air temperature - Dolly L. Hall-Quinlan; Hao He; Xinrong Ren; Timothy P. Canty; Ross J. Salawitch; Phillip Stratton; Russell R. Dickerson (Atmospheric Environment, 2023)

Ultra-low-level measurements of airborne fission products from the Fukushima Daiichi reactor accident using high volume collection systems at Savannah River National Laboratory - James R. Cadieux; Brent Fallin; Heather A. Brant; Timothy B. Brown; Robert L. Buckley; Gregory Hall; George S. King; Ashlee Swindle (Journal of Environmental Radioactivity, 2023)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Dumpsters and other anthropogenic structures as habitat for invasive African rock agama lizards in Florida - Timothy S. Mitchell; Brian Folt; Joshua M. Hall (Biological Invasions, 2021)

Dependence on a human structure influences the extinction of a non-native lizard population after a major environmental change - Daniel A. Warner; Joshua M. Hall; Amélie Fargevieille; Austin C. Hulbert; Sarin Tiatragul; Jenna E. Pruett; Timothy S. Mitchell (Biological Invasions, 2021)

Mitigating eutrophication and toxic cyanobacterial blooms in large lakes: The evolution of a dual nutrient (N and P) reduction paradigm - Hans W. Paerl; Karl E. Havens; Hai Xu; Guangwei Zhu; Mark J. McCarthy; Silvia E. Newell; J. Thad Scott; Nathan S. Hall; Timothy G. Otten; Boqiang Qin (Hydrobiologia, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Use of human-made structures facilitates persistence of a non-native ectotherm - Austin C. Hulbert; Joshua M. Hall; Timothy S. Mitchell; Daniel A. Warner (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Low salinity as a biosecurity tool for minimizing biofouling on ship sea chests - Maria Cecilia T. de Castro; Thomas Vance; Anna L. E. Yunnie; Timothy W. Fileman; Jason M. Hall-Spencer (Ocean Science, 2018)
Biofouling is a major vector in the transfer of non-native species around the world. Species can be transported on virtually all submerged areas of ships (e.g. hulls, sea chests, propellers) and so antifouling systems are used to reduce fouling. However, with increased regulation of biocides used in antifoulants (e.g. the International Maritime Organization tributyltin ban in 2008), there is a need to find efficient and sustainable alternatives. Here, we tested the hypothesis that short doses of low salinity water could be used to kill fouling species in sea chests. Settlement panels were suspended at 1.5 m depth in a Plymouth marina for 24 months by which time they had developed mature biofouling assemblages. We exposed these panels to three different salinities (7, 20 and 33) for 2 hours using a model sea chest placed in the marina and flushed with freshwater. Fouling organism diversity and abundance were assessed before panels were treated, immediately after treatment, and then 1 week and 1 month later. Some native ascidian Dendrodoa grossularia survived, but all other macrobenthos were killed by the salinity 7 treatment after 1 week. The salinity 20 treatment was not effective at killing the majority of fouling organisms. On the basis of these results, we propose that sea chests be flushed with freshwater for at least 2 hours before ships leave port. This would not cause unnecessary delays or costs and could be a major step forward in improving biosecurity.

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Female investment in offspring size and number shifts seasonally in a lizard with single-egg clutches - Timothy S. Mitchell; Joshua M. Hall; Daniel A. Warner (Evolutionary Ecology, 2018)

Genomic deletions and mutations resulting in the loss of eight genes reduce the in vivo replication capacity of Meleagrid herpesvirus 1 - Timothy J. Mahony; Robyn N. Hall; Stephen Walkden-Brown; Joanne Meers; Jennifer L. Gravel; Lani West; Vanessa Hardy; A.F.M. Fakhrul Islam; Elizabeth V. Fowler; Neena Mitter (Virus Genes, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Trace elements and major ions in atmospheric wet and dry deposition across central Illinois, USA - Mary M. Lynam; J. Timothy Dvonch; Naima L. Hall; Masako Morishita; James A. Barres (Air Quality, Atmosphere & Health, 2015)

Spatial patterns in wet and dry deposition of atmospheric mercury and trace elements in central Illinois, USA - Mary M. Lynam; J. Timothy Dvonch; Naima L. Hall; Masako Morishita; James A. Barres (Environmental Science and Pollution Research, 2014)

Time and space in biogeography: response to Parenti & Ebach (2013) - Mark de Bruyn; Björn Stelbrink; Timothy J. Page; Matthew J. Phillips; David J. Lohman; Christian Albrecht; Robert Hall; Kristina von Rintelen; Peter K.L. Ng; Hsi‐Te Shih; Gary R. Carvalho; Thomas von Rintelen (Journal of Biogeography, 2013)
A recent Guest Editorial by Parenti & Ebach (2013, Journal of Biogeography , 40, 813–820) disagrees with the methods or interpretations in two of our recent papers. In addition, the authors open a debate on biogeographical concepts, and present an alternative philosophy for biogeographical research in the context of their recently described biogeographical subregion called ‘Pandora’. We disagree with their approach and conclusions, and comment on several issues related to our differing conceptual approaches for biogeographical research; namely, our use of molecular phylogenetic analyses, including time estimates; and Parenti & Ebach's reliance on taxon/general area cladograms. Finally, we re‐examine their ‘tests’ supporting the existence of ‘Pandora’.

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Idealized tracer transport models with time-varying transport: applications to ocean boundary currents - F. Terenzi; Timothy M. Hall (Environmental Fluid Mechanics, 2010)

Multi-scale landscape factors influencing stream water quality in the state of Oregon - Maliha S. Nash; Daniel T. Heggem; Donald Ebert; Timothy G. Wade; Robert K. Hall (Environmental Monitoring and Assessment, 2009)

Trade‐Offs in the Design of Fishery Closures: Management of Silky Shark Bycatch in the Eastern Pacific Ocean Tuna Fishery - JORDAN T. WATSON; TIMOTHY E. ESSINGTON; CLERIDY E. LENNERT‐CODY; MARTIN A. HALL (Conservation Biology, 2009)
Bycatch—the incidental catch of nontarget species—is a principal concern in marine conservation and fisheries management. In the eastern Pacific Ocean tuna fishery, a large fraction of nonmammal bycatch is captured by purse‐seine gear when nets are deployed around floating objects. We examined the spatial distribution of a dominant species in this fishery's bycatch, the apex predator silky shark ( Carcharhinus falciformis ), from 1994 to 2005 to determine whether spatial closures, areas where fishing is prohibited, might effectively reduce the bycatch of this species. We then identified candidate locations for fishery closures that specifically considered the trade‐off between bycatch reduction and the loss of tuna catch and evaluated ancillary conservation benefits to less commonly captured taxa. Smoothed spatial distributions of silky shark bycatch did not indicate persistent small areas of especially high bycatch for any size class of shark over the 12‐year period. Nevertheless, bycatch of small silky sharks (

PvALF and FUS3 activate expression from the phaseolin promoter by different mechanisms - Danny W-K Ng; Timothy C. Hall (Plant Molecular Biology, 2008)

Organization, not duplication, triggers silencing in a complex transgene locus in rice - Guojun Yang; Yeon-Hee Lee; Yiming Jiang; Siva P. Kumpatla; Timothy C. Hall (Plant Molecular Biology, 2005)

Interaction of PvALF and VP1 B3 domains with the β-phaseolin promoter - Raúl Carranco; Mahesh Chandrasekharan; James Townsend; Timothy Hall (Plant Molecular Biology, 2004)

Molecular Characterization of Duck Hepatitis B Virus Isolates from South African Ducks - Nomathibane P. Mangisa; Heidi E. Smuts; Anna Kramvis; C. Wendy Linley; Michelle Skelton; Timothy J. Tucker; Pauline De La M. Hall; Del Kahn; Allison R. Jilbert; Michael C. Kew (Virus Genes, 2004)

Characterization of two rice DNA methyltransferase genes and RNAi-mediated reactivation of a silenced transgene in rice callus - Mahesh B. Chandrasekharan; Yiming Jiang; Jarunya Narangajavana; Timothy C. Hall; Prapapan Teerawanichpan (Planta, 2004)

The 5′ UTR negatively regulates quantitative and spatial expression from the ABI3 promoter - Danny W-K Ng; Mahesh B. Chandrasekharan; Timothy C. Hall (Plant Molecular Biology, 2004)

The Impact of Twenty-First Century Climate Change on Wildland Fire Danger in the Western United States: An Applications Perspective - Timothy J. Brown; Beth L. Hall; Anthony L. Westerling (Climatic Change, 2004)

MDM -1 and MDM -2: Two Mutator -Derived MITE Families in Rice - Guojun Yang; Timothy C. Hall (Journal of Molecular Evolution, 2003)

Chromatin structure and phaseolin gene regulation - Guofu Li; Mahesh B. Chandrasekharan; Alan P. Wolffe; Timothy C. Hall (Plant Molecular Biology, 2001)

Fluorescence in situ hybridization of single copy transgenes in rice chromosomes - Pushpa Kharb; Jinjiang Dong; M. N. Islam-Faridi; David M. Stelly; Timothy C. Hall (In Vitro Cellular & Developmental Biology - Plant, 2001)

Transgene silencing in monocots - Lakshminarayan M. Iyer; Siva P. Kumpatla; Mahesh B. Chandrasekharan; Timothy C. Hall (Plant Molecular Biology, 2000)

Effects of prolonged iron loading in the rat using both parenteral and dietary routes. - Wanida Chua-anusorn; David J. Macey; John Webb; Pauline de la Motte Hall; Timothy G. St. Pierre (BioMetals, 1999)

Transgenic Over-Expression of a Motor Protein at High Levels Results in Severe Cardiac Pathology - Jeanne James; Hanna Osinska; Timothy E. Hewett; Thomas Kimball; Raisa Klevitsky; Sandra Witt; D. Greg Hall; James Gulick; Jeffrey Robbins (Transgenic Research, 1999)

Longevity of 5-azacytidine-mediated gene expression and re-establishment of silencing in transgenic rice - Siva P. Kumpatla; Timothy C. Hall (Plant Molecular Biology, 1998)

Spontaneous but not experimental metastatic activities differentiate primary tumor-derived vs metastasis-derived mouse prostate cancer cell lines - Simon J. Hall; Timothy C. Thompson (Clinical & Experimental Metastasis, 1997)

The β-phaseolin 5′ matrix attachment region acts as an enhancer facilitator - Apolonia H.M. van der Geest; Timothy C. Hall (Plant Molecular Biology, 1997)